2002
DOI: 10.1046/j.0014-2956.2001.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Pichia pastoris‐derived recombinant pro‐Der p 1 induced by deglycosylation and by the natural cysteine protease Der p 1 from house dust mite

Abstract: The mature cysteine protease from Dermatophgoides pteronyssinus, Der p 1, is a major house dust mite allergen. Its enzymatic activity has been shown to have pro‐inflammatory effects that could also negatively influence efficacy of allergen‐specific immunotherapy. The aim of this study was to express recombinant pro‐Der p 1 (rpro‐Der p 1) in the yeast Pichia pastoris and to study its maturation. Expression was achieved at a concentration ranging from 45 mg·L−1 (methanol‐induced expression) to 168 mg·L−1 (consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 37 publications
(44 reference statements)
2
49
3
Order By: Relevance
“…This observation is in good agreement with that of previous studies of the influence of glycosylation on the activation process. This hypothesis could also explain the different results reported by Jacquet et al and van Oort et al 16,17 van Oort et al did not succeed in obtaining maturation of WT recombinant ProDer p 1 with the correct N terminus, 17 whereas Jacquet et al reported that the WT ProDer p 1 lacking the first 19 residues was easily converted into mature allergen after acidic treatment. 16 However, the fact that the ProDer p 1 N52Q mutant also presents the ATFE intermediate at the end of the production may be attributed to the heterogeneous glycosylation of the propeptide as previously proposed.…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…This observation is in good agreement with that of previous studies of the influence of glycosylation on the activation process. This hypothesis could also explain the different results reported by Jacquet et al and van Oort et al 16,17 van Oort et al did not succeed in obtaining maturation of WT recombinant ProDer p 1 with the correct N terminus, 17 whereas Jacquet et al reported that the WT ProDer p 1 lacking the first 19 residues was easily converted into mature allergen after acidic treatment. 16 However, the fact that the ProDer p 1 N52Q mutant also presents the ATFE intermediate at the end of the production may be attributed to the heterogeneous glycosylation of the propeptide as previously proposed.…”
Section: Discussioncontrasting
confidence: 47%
“…17,18 In this study, we investigated the influence of the different potential N-glycosylation sites in the maturation process and the pH influence on the propeptide association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed preference for small aliphatic residues and charged residues in subsites S2 and S1, respectively, is of particular interest because proDer p 1 is cleaved after the A79-E80 sequence during maturation. It is therefore plausible that mature Der p 1 is capable of activating other proDer p 1 molecules, which experiments using nDer p 1 to process rproDer p 1 have shown (47). The theoretical isoelectric point of mature wt Der p 1 (Swiss-Prot P08176) is 5.6 in contrast to the classical papaya cysteine endopeptidases, which have a basic theoretical pI (e.g., 9.6 for papain, P00784).…”
Section: Discussionmentioning
confidence: 88%
“…Glycosylations on natural and recombinant (P. pastoris) Der p 1 and Der f 1, resulting in a large molecular mass smear for the recombinant proteins, have been reported by a number of groups (16,17,(47)(48)(49). By mutating the potential glycosylation site at N132 and N133 in the mature region of proDer p 1 and proDer f 1, respectively, this smear can be shifted into distinct bands with a lower molecular mass in SDS-PAGE (17,49).…”
Section: Discussionmentioning
confidence: 99%